Green Synthesis of ZnO/Ag Nanocomposite using Psidium guajava: A Study on Characterization and Potential Clinical Application as Advanced Antibacterial Agents on Cotton Bandages - Khairunnisa, Yasmin Hasna; Kunarti, Eko Sri; Nuryono, Nuryono (Universitas Gadjah Mada, 2026)
The development of innovative green antibacterial agents has been proposed as a strategy to combat bacterial resistance and improve wound healing. This research explores the synthesis of ZnO/Ag nanocomposites using guava leaf extract and evaluates their antibacterial properties. The study focused on optimizing ZnO nanoparticle synthesis by adjusting precursor concentrations, followed by Ag modification through variations in Ag precursor levels, pH, and reaction times to achieve optimal ZnO/Ag nanocomposites properties. The optimized ZnO and ZnO/Ag materials were applied to cotton bandages, and both the nanomaterials and the coated bandages were characterized using FTIR, SEM, TEM, and UV-vis-NIR, with their antibacterial activity tested against Staphylococcus aureus and Escherichia coli. The optimal synthesis conditions were identified as 0.60 M ZnO, 1% Ag, 2 h, and pH 12. The characterization results verified the successful synthesis of the ZnO/Ag nanocomposite and its effective coating on cotton bandages. Antibacterial test revealed that the ZnO/Ag demonstrated significantly greater activity than ZnO alone, with inhibition zones measuring 21.35 mm for S. aureus and 3.85 mm for E. coli. These outcomes highlight the potential of biosynthesized nanomaterials for use in clinical wound dressings to promote wound healing.